(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Zinc oxide nanoparticles (ZnO NPs) synthesized using extracts from medicinal plants were characterized and evaluated for their antimicrobial properties. Scanning electron microscopy (SEM) and Zeta sizer were used for characterization and to study the size. The nanoparticles exhibited significant antibacterial activity against a range of pathogens, including bacteria. These results suggest that ZnO NPs synthesized from medicinal plant extracts hold promise for applications in medicine and environmental remediation. Zinc oxide nanoparticles (ZnO NPs) synthesized via green synthesis using medicinal plant extracts have emerged as an eco-friendly and cost-effective alternative to traditional synthesis methods. Green synthesis involves using plant-based materials, which act as both reducing and stabilizing agents, eliminating the need for harsh chemicals and high energy inputs typically associated with chemical or physical synthesis processes.